Beliefs about Causes and Consequences of Obesity among Women in Two Mexican Cities (Journal of Health, Population and Nutrition, 2012)
Personal beliefs might be barriers to the prevention and treatment of obesity. To assess the beliefs about causes and consequences of and possible solutions to obesity among 18-40 years old women in two Mexican cities and to analyze the association with demographic variables, we developed a questionnaire and assessed the womens weight status. The questionnaire was applied at two outpatient healthcare centres and assessed the responses by the Likert scale. Results were analyzed by demographics, using the chi-square and Spearman correlations. One thousand one hundred adult women participated in the study. Mean age was 27.8 years, and mean BMI (kg/m2) was 27.05. The prevalence of overweight and obesity was 35% and 24% respectively. The most mentioned causes of obesity were eating oil and fat (4.1), fried foods (4.1), and eating too much (4.00). The most reported consequences were diseases (4.1), discrimination (3.9), and early death (3.7). The main solutions were physical activity (4.2), healthful eating (4.2), and personal motivation (4.1). Age of participants higher than 30 years, living with a partner, having more than 6 years of education, and having overweight and obesity were predictors of more knowledge about the causes, consequences, and solutions. These Mexican women from low SES had reasonably good knowledge about the causes and consequences of obesity. Although improving education might be beneficial to prevent obesity, changes in environmental contingencies are also necessary to prevent this epidemic. DOI: http://dx.doi.org/10.3329/jhpn.v30i3.12295 J HEALTH POPUL NUTR 2012 Sep;30(3):311-316